MAANGO: PENDIDIKAN MASYARAKAT NEGERI GAYO DALAM HASANAH SYARI’AT ISLAM DAN ADAT - Zulkarnain, Zulkarnain; Akbar, Eliyyil (EDUKASIA, 2018)
Islam was originally used as a living joint manifested in the customs of the Acehnese people who then switched to following the system of government that resulted in the decline of the religious adaptation of Islam. Shifting of Islamic values to Syari'ah enforcement regions resulted in conflict. Aceh is able to rise to prioritize the syari'ah of Islam to be a mecca in the case and make a custom in life. Gayo which is one of the areas in Aceh to develop the Aceh Gayo Traditional Assembly so that the value of Islam and customs in line in educating the community into a khalifah. This paper reviews the concept of MAANGo in preparing a dignified society on the aspects of life in Islamic and customary hasanah law. and to know the results of institutional tasks in educating people based on Islamic and customary law. MAANGo as an institution in tradition establishing  by breathing Shari'ah in accordance with the condition of the region that prioritizes Islamic values. The concept in dealing with the behavior of society that in fact is changing is by making education as the front guard to doctrine mindset and behavior according to custom syariat through the field of customary law, the field of assessment, education and development, conserving library or guidance of customs and empowerment of women. The result in carrying out the mandate as an tradition institution to build the smoothness of government duties, conservation of customary law values and to maintain harmony in social matters.